1998
DOI: 10.1103/physreve.58.r5217
|View full text |Cite
|
Sign up to set email alerts
|

Disorder, order, and domain wall roughening in the two-dimensional random field Ising model

Abstract: Ground states and domain walls are investigated with exact combinatorial optimization in two-dimensional random field Ising magnets. The ground states break into domains above a length scale that depends exponentially on the random field strength squared. For weak disorder, this paramagnetic structure has remnant longrange order of the percolation type. The domain walls are super-rough in ordered systems with a roughness exponent close to 6/5. The interfaces exhibit rare fluctuations and multiscaling reminisce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
44
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 31 publications
6
44
0
Order By: Relevance
“…These arguments led to a critical dimension d c = 2. Numerical evidence [19,20] shows roughening of domain walls and the ground state breaking into domains above a length scale that depends exponentially on the random field strength squared, further strengthened the argument that d c = 2. Experiments on 2d dilute antiferromagnets, showed that no long-range ordering is present [21,22], but a possibility of first order transition in 3d has been observed [23].…”
Section: Introductionmentioning
confidence: 83%
“…These arguments led to a critical dimension d c = 2. Numerical evidence [19,20] shows roughening of domain walls and the ground state breaking into domains above a length scale that depends exponentially on the random field strength squared, further strengthened the argument that d c = 2. Experiments on 2d dilute antiferromagnets, showed that no long-range ordering is present [21,22], but a possibility of first order transition in 3d has been observed [23].…”
Section: Introductionmentioning
confidence: 83%
“…1͒. 20,21 This means that the surfaces have a tendency to be ordered "as such," and to see the true ordinary transition behavior, one needs L Ͼ L b . Thus, we use substantially weakened surface interactions J 1 Ӷ J to circumvent this problem.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The study of the exact ground state of the RFIM has been possible due to the existence of a well-established equivalence between the problem of finding the ground state of the Hamiltonian (1) and the problem of finding the cut with minimum capacity of a network [1][2][3]. Using this mapping, many numerical efforts have been devoted to the understanding of how the ground state properties change when the amount of disorder σ is changed for the 2d [4,5] and 3d [6] Gaussian RFIM. In this paper we propose an algorithm that allows us to go one step forward and study the properties of the first excited state (FES) of the Hamiltonian (1).…”
Section: Introductionmentioning
confidence: 99%